Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5114/ms.2016.61102
|View full text |Cite
|
Sign up to set email alerts
|

Coronary embolism causing acute myocardial infarction. Review of the literature

Abstract: Coronary artery embolism (CE) should be considered as a nonatherosclerotic cause of acute myocardial infarction (AMI), especially in patients with conditions favouring the formation of intracardiac thrombi. The main aetiologies of CE have changed in recent decades. Currently, atrial fibrillation is the most common cause. Most studies on CE infarcts are case reports with small numbers of patients. There are still no clear guidelines for the management in embolic myocardial infarction. Depending on the aetiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…The main cause of CS in the early hours of STEMI is acute left ventricular failure resulting from a massive necrosis or some combination of a moderate necrosis and muscle freezing in the adjacent areas. Mechanical complications of MI as well as other rare cause are also reported [2]. The SHOCK trial clearly showed benefits from the use of an early revascularization strategy.…”
Section: Introductionmentioning
confidence: 98%
“…The main cause of CS in the early hours of STEMI is acute left ventricular failure resulting from a massive necrosis or some combination of a moderate necrosis and muscle freezing in the adjacent areas. Mechanical complications of MI as well as other rare cause are also reported [2]. The SHOCK trial clearly showed benefits from the use of an early revascularization strategy.…”
Section: Introductionmentioning
confidence: 98%
“…-4,3% (4) . Zatorowość tętnic wieńcowych jako potencjalną przyczynę ostrego zespołu wieńcowego należy podejrzewać u pacjentów bez choroby miażdżycowej udowodnionej w koronarografii, ale z czynnikami ryzyka sprzyjającymi powstawaniu skrzeplin wewnątrzsercowych (5) . Etiologia zatorowości tętnic wieńcowych na przestrzeni lat się zmieniła.…”
Section: Omówienieunclassified
“…At the time of angiography, no clinically overt specific cause is present. bility or rare cases of paradoxical embolisation [11]. The guidelines do not include peri-partum cardiomyopathy (PPCM) as a potential trigger of MINOCA; however, a presentation of typical acute retrosternal chest pain in a young breast-feeding female together with STEMI pattern on ECG and significant cTn rise is highly suggestive of acute MI, and many such patients undergo coronary angiography.…”
Section: Pregnancy 2018mentioning
confidence: 99%